Classroom Management in Learning Islamic Religious Education at SD Nurul Amin Islamic School Bekasi City - Wildan Miftah Firdaus; Ferianto (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
Teacher skills are not only from the teacher's ability to master the material, but also the teacher must be able to manage the class well so that learning can run effectively and efficiently. This study uses a qualitative method. The research was conducted at SD Nurul Amin Islamic School Bekasi City. The results showed that the teacher in grade 2 SD Nurul Amin Islamic School Bekasi City in classroom management in learning Islamic religious education used an authoritarian approach. Teachers in grade 2 SD Nurul Amin Islamic School Bekasi City apply classroom rules in fostering discipline in Islamic religious education learning, such as: habituation before learning begins; Students are required to follow the flagship Tahfidz program; students keep books and throw trash in their place, enter class on time and do homework as instructed; the application of punishment such as writing istighfar or memorizing verses of the Qur'an. Barriers in the management of grade 2 SD Nurul Amin Islamic School is known that students still tend to like to play during the learning takes place. The solution to these obstacles, the teacher must choose the right approach and method to create a conducive classroom environment. The purpose of this study is that it is expected to motivate teachers to remember the importance of fostering children's discipline and it is hoped that teachers can create good classroom management to achieve the expected learning objectives.